극단적인 네트워크 환경을 위한 효율적인 라우팅 알고리즘 - 왕종수; 서두옥; Wang, Jong Soo; Seo, Doo Ok ((사)디지털산업정보학회 논문지, 8(1), 2012)
Sensor networks and car networks that have different structure from that of conventional TCP/IP network require extreme network environment due to frequent change of connectivity. Because such extreme network environment has characteristics like unreliable link connectivity, long delay time, asymmetrical data transfer rate, and high error rate, etc., it is difficult to perform normally with the conventional TCP/P-based routing. DTNs (delay and disruption tolerant network) was designed to support data transfer in extreme network environment with long delay time and no guarantee for continuous connectivity between terminals. This study suggests an algorithm that limits the maximum number of copying transferred message to L by improving the spray and wait routing protocol, which is one of the conventional DTNs routing protocols, and using the azimuth and density data of the mobile nods. The suggested algorithm was examined by using ONE, a DTNs simulator. As a result, it could reduce the delay time and overhead of unnecessary packets compared to the conventional spray and wait routing protocol.